Soil organic carbon build up in sesame under soybean-sesame cropping systems in response to organic management modules: Soil organic carbon build up in sesame under soybean-sesame cropping systems in response to organic management modules - K RAMESH; AZIZ QURESHI; P DURAIMURUGAN; PRADUMAN YADAV; PC LATHA; T BOOPATHI; C MANIMURUGAN; SANKARI MEENA (Journal of Oilseeds Research, 2023)
Field experiments were conducted in deep Vertisols at ICRISAT farm in a fixed plot with eight nutrient management options with complete organic package to understand the soil organic carbon build-up since 2018 for soybean (cv. Basara) - sesame (cv. Swetatil) cropping system have shown that application of castor cake has maintained a soil organic carbon content indicating that the castor cake may be utilised as an organic nutrient source for sesame crop under vertisols of Hyderabad, Telangana.